The impact of digital finance on green economic development: A literature review - Li, Chun; Alasinrin Babatunde, Kazeem (Edelweiss Applied Science and Technology, 2024)
Green economic development has become an essential pathway to achieving high-quality economic growth, while digital finance represents a prominent trend in global financial advancement. The rapid expansion of digital finance in China has spurred extensive research in this domain. This study systematically combes the literature on digital finance and green economic development. Initially, it delineates the conceptual definition of digital finance, measurement indices and the conceptual definition of green economic development, identifies the key influencing factors. Subsequently, it synthesizes empirical findings on how digital finance influences the growth of green economy from economic, environmental, and energy perspectives. The economic perspective is divided into macroeconomic impacts, mechanisms of influence, and microeconomic aspects; the environmental perspective focuses on the pollution effects and carbon emission reduction attributable to digital finance, and the energy perspective reviews literature on improvements in energy efficiency and reductions in energy intensity driven by digital finance. Finally, the paper offers a comprehensive summary of current research trends and future directions in the field. It emphasizes the need for enhanced digital finance index systems, robust risk control and regulation, and a balanced approach to fostering a genuine green economy. Additionally, it highlights potential future research avenues, such as the effects of digital finance on government policies, foreign trade, environmental pollution, and energy utilization.